ANALISIS YURIDIS PENGGUNAAN LEMBAGA CESSIE DALAM PERJANJIAN KREDIT JAMINAN KIOS PADA PT. BANK DANAMON INDONESIA - JUANTO PADANG (PREMISE LAW JURNAL, 2017)
DOSEN PEMBIMBING:1. Sunarmi2. Muhd Yamin3. T. Keizerina DeviA Various kinds of collateral in banking system cannot be separated from thedynamic business development. One of them is stalls as collateral. A stall cannotbe categorized as real property rights as stipulated in Book II of the Civil Code sothat the binding of credit security for a stall cannot use real property rightinstitution such as hypothecation, mortgage, pawn, and fiduciary. Therefore, theabsence of norm will be substituted with cessie institution in banking system in acredit contract for stalls. What factors which influence the use of cessie and howabout the legal domicile and consequence for a Bank as creditor are analyzedbased on legal provisions on collateral. The use of cessie institution in thebinding of stalls as collateral has its legal consequence that the bank legaldomicile toward the stalls as collateral is only as unsecured creditor so thatjuridically it cannot give security for paying off credit because it does not haveany executorial power as intended by credit security institution. When a debtordefaults, creditor will have difficulty to cash the collateral of the stalls. In thiscase, legal protection for creditor is weak.Keywords: Cessie, Collateral, Stalls